Synthesis and Antimicrobial Activity ofSome New Thioether Derivatives of Quinoxaline - D. C. P. Singh; S. R. Hashim; R. G. Singhal (E-Journal of Chemistry)
2-Chloro-3-methylquinoxaline was selected as nucleus around which the molecular manipulations were carried out to get new compounds expected to possess better anti microbial activity. Various quinoxaline derivatives have been synthesized by replacing the chlorine at C-2 with a thioether linkage, which in turn attached to 2-(N-(substituted phenyl)acetamides. The synthesized compounds (5) were tested for their antimicrobial activity. Compounds 5b, 5c, 5d and 5i were found most active (comparable to the standard antibacterial Ciprofloxacin) amongst them. The structure of the compounds was confirmed on the basis of their spectral data.